P. Phillips family papers - Phillips, P. (Philip), 1807-1884.; Levy, Fanny Yates, 1787-1891 or 1892.; Levy, Jacob Clavius, 1788-1875.; Phillips, Eugenia Levy.; Phillips, W. Hallett (William Hallet), 1853-1897.
Correspondence, letterbooks, legal record books, journals, dockets, notebooks, photographs, and other papers relating chiefly to the legal careers of P. Phillips and his son, W. Hallet Phillips. Documents their practice of law in Washington, D.C., in particular their practice before the Supreme Court. Includes an unpublished autobiography of P. Phillips; journal of his wife, Eugenia Levy Phillips, written while interned as a Southern sympathizer during the Civil War; and papers of her parents, Jacob Clavius Levy and Fanny Yates Levy. The P. Phillips papers concern California and the United States and Mexican Claims Commission, slave trade and Key West, Fla., judicial reform, repeal of the Missouri compromise, and passage of the Kansas-Nebraska Act. The W. Hallet Phillips papers concern Yellowstone National Park; the rights of the Moki (Hopi) Indians of Arizona; a lynching in Hahnville, La.; and the Cuban Revolution, 1895-1898. Correspondents include James B. Campbell, Edmund Strother Dargan, John Forsyth, George Wilkins Guthrie, John Marshall Harlan, William R. King, L.Q.C. Lamar, John Theodore Ludeling, Medill McCormick, M.C. Mordecai, Richard Olney, Hoke Smith, Edwin McMasters Stanton, A.B. Stickney, and William Yerger.
Lawyer, state legislator, and U.S. representative from South Carolina.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Campbell, James B., -- 1808-1883 -- Correspondence; Dargan, Edmund Strother, -- 1805-1879 -- Correspondence; Forsyth, John, -- 1780-1841 -- Correspondence; Guthrie, George Wilkins, -- 1848-1917 -- Correspondence; Harlan, John Marshall, -- 1833-1911 -- Correspondence; King, William R. -- 1786-1853 -- Correspondence; Lamar, L. Q. C. -- 1825-1893 -- Correspondence; Ludeling, John Theodore, -- 1827-1891 -- Correspondence; McCormick, Medill, -- 1877-1925 -- Correspondence; Mordecai, M. C. -- 1804-1888 -- Correspondence; Olney, Richard, -- 1835-1917 -- Correspondence; Smith, Hoke, -- 1855-1931 -- Correspondence; Stanton, Edwin McMasters, -- 1814-1869 -- Correspondence; Stickney, A. B. -- 1840-1916 -- Correspondence; Yerger, William, -- 1816-1872 -- Correspondence; Phillips family; United States. -- Supreme Court; United States and Mexican Claims Commission; United States; Courts -- United States; Hopi Indians; Indians of North America -- Arizona; Justice, Administration of; Lynching -- Louisiana -- Hahnville; Missouri compromise; National parks and reserves; Practice of law -- Washington (D.C.); Slave trade -- United States; California -- History; Cuba -- History -- Revolution, 1895-1898.; Key West (Fla.) -- History; Mexico -- Claims vs. United States; United States -- Claims vs. Mexico; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; Yellowstone National Park; Lawyers; Legislators -- South Carolina; Representatives, U.S. Congress -- South Carolina